Forgotten digital tourniquet - Sardenberg, Trajano [UNESP]; Neto, Pedro Sarzi [UNESP]; Varanda, Denis [UNESP]; Cortopassi, Andrea Christina [UNESP] (My University, 2024)
Introduction: Minor surgeries on fingers and toes can be performed with the aid of a digital tourniquet. Forgotten tourniquet is a rare but catastrophic complication. Objectives: To assess cases of forgotten digital tourniquets through a systematic review. Methods: Articles were searched in PubMed, Embase, Web of Science, Scopus and Cochrane databases. A combination of terms related to the digital tourniquet was used. Country of event, language, sex, age, patient origin (public service cases or other cases), affected finger, diagnosis or previous surgery, type of tourniquet, whether it was emergency or elective surgery, time of forgetfulness, presence or absence of pain, treatment performed and results were noted. Results: Thirteen articles with 16 case reports of forgotten finger tourniquets were selected from 1973 to 2021. The most commonly used type of tourniquet was the glove finger, and the time of abandonment ranged from 36 hours to 14 days. Treatments involved antithrombotic medication, vasodilators, microsurgeries, and leeches. Two cases resulted in amputation, nine had functional loss, three reported no sequelae, and four did not present information. Conclusions: It is recommended not to use the glove finger tourniquet. The treatment of ischemia and gangrene should be individualized.
El olvido del torniquete digital
Keywords: complication; finger; gangrene; ischemia; tourniquet